(:unas) unassigned - Georgiadou, Olga (My University, 2018)
Design of a wiki, containing online material for the Foreign Languages taught at the Cyprus University of Technology Language Centre. Participation in the designing of the page of English for Academic Purposes, the pages of English for A1 and A2 levels of CEFR for languages and French for A1 level of CEFR for languages.